Lecturer’s Encouragement Factors Influencing EFL Students’ Willingness to Communicate in Speaking Class - Alawiyah, Siti; Salija, Kisman; Korompot, Chairil Anwar (Celebes Journal of Language Studies, 2024)
This qualitative research aimed to explore the lecturer’s encouragement factors influencing EFL students’ WTC in speaking class. Participants of this research were a lecturer and students who took a public speaking course in the fifth semester of the English Education Department at Yayasan Pendidikan Ujung Pandang. The data was collected through observation notes and semi-structured interviews. The finding of this research revealed that lecturer’s encouragement factors that influence students’ willingness to communicate in speaking class were the lecturer’s decision on the topic, the lecturer’s support, the lecturer’s positive feedback, and the lecturer’s appreciation. In addition, based on the students’ perceptions, the lecturer’s encouragement factors that influence their willingness to communicate in speaking class were increasing their self-confidence and participation in speaking class.